PENGGUNAAN MEDIA AUDIO VISUAL PADA PEMBELAJARAN TEMA 2 SELALU BERHEMAT ENERGI SUBTEMA 1 PEMBELAJARAN 1 UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDI NAIMATA KOTA KUPANG - Noeng, Theresia A. M. C.; Taneo, Silvester P.; Adoe, Treesly Y.N. (Journal of Character and ELementary Education, 2024)
This research was carried out at SDI Naimata, Kupang City with the aim of "To improve learning outcomes in learning Theme 2 Always Save Energy Sub-theme 1 Lesson 1 for fourth grade students at SDN Naimata in determining main ideas and supporting ideas using audio visual media." Data collection techniques are observation techniques and test techniques. Subjects, namely Techniques. Research subjects or respondents are the parties used as samples in a study. The research subject also discusses the characteristics of the subjects used in the research, including an explanation of the population, sample and sampling technique used. Data Analysis is a technique regarding the way the researcher analyzes data, with the research results showing that the data resulting from observing teacher activity in cycle I is of value. 62.5% while in cycle II with a value of 82.69%, while the results of observing student activities in cycle I had an average value of 61.80%, while the results of observing student activities in cycle II had an average value of 81.40%. In the first cycle of learning, there were 25 students from the subject, of which 17 people (68%) then 8 people (32%) did not complete it. Furthermore, in cycle II learning outcomes increased, namely from 25 students, all of them completed (100%). Based on the results of the research above, it is known that learning Indonesian uses audio-visual media. This is proven by the increase in learning outcomes in cycle II, namely 100%, thus the use of audio visual media in theme 2 learning always saves energy in subtheme 1 learning 2 to improve the learning outcomes of class IV students at SDI Naimata, Kupang City.